2020
DOI: 10.1039/d0ra00415d
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium on phosphorous-modified alumina as an effective and stable catalyst for catalytic transfer hydrogenation of furfural

Abstract: Phosphorous induces structural changes in Ru/Al2O3 that make it more active and more stable for liquid phase hydrogenation of furfural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
2
11
1
Order By: Relevance
“…These TPR results are opposed to reports on Pd and Ru were the presence of P resulted in increased electron density and reducibility [24,26]. However, recent studies devoted to investigate poisoning effects also observed a decrease of reducibility in similar Pt-based samples in the presence of P [31,32].…”
Section: Characterisationcontrasting
confidence: 91%
See 3 more Smart Citations
“…These TPR results are opposed to reports on Pd and Ru were the presence of P resulted in increased electron density and reducibility [24,26]. However, recent studies devoted to investigate poisoning effects also observed a decrease of reducibility in similar Pt-based samples in the presence of P [31,32].…”
Section: Characterisationcontrasting
confidence: 91%
“…The conversion of furfural to acetals and ethers is known to require Brønsted acid sites on the alumina surface [37]. Previous reports on P modified Ru/Al 2 O 3 claim that addition of P generates Brønsted sites on the support [24]. The formation of FA ether in Al 2 O 3 -Pt-2P could hence also be related to an increased support acidity.…”
Section: Furfural Hydrogenationmentioning
confidence: 97%
See 2 more Smart Citations
“…Ru/Al 2 O 3 was also used in the liquid phase catalytic hydrogenation of FAL in a recent study [63]. These catalysts were modified with phosphorous to improve Ru stability against leaching.…”
Section: Hydrogenationmentioning
confidence: 99%